Autoestima y prácticas de Autocuidado en el adulto maduro hospitalizado del Centro Médico Especializado Casa Grande - ESSALUD - Torres Alayo, Patricia Geraldine (2019)
SUMMARY The present research work of descriptive correlational type; of cross section, was carried out with the aim of determining the relationship between the level of self-esteem and practices of self-care in the mature adult of the Specialized Medical Center Casa Grande-EsSalud between the months of June to August 2018; in a sample population of 46 mature adults aged 40 to 59 years. The instruments used to collect the information were: The Self-esteem Scale and the Questionnaire on Self-Care Practices. For the analysis of the data obtained, the nonparametric statistical test of independence of chi-square criteria was applied. Reaching the following conclusions: 68 percent of mature adults have a positive self-esteem level and 32 percent negative. 65 percent of mature adults have adequate self-care practices and 35 percent are inadequate. There is a significant relationship between self-esteem level and self-care practices in the mature hospitalized adult; the nonparametric test of independence of chi-square criteria X2 = 0.941 p-value = 0.332